Pengaruh Slack Resources, Sensitivitas Industri, dan Kinerja Lingkungan terhadap Corporate Social Responsibility Disclosure : (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Prilya Stevania Imkotta; Linda Grace Loupatty; Senda Yunita Leatemia (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to examine and analyze the factors influencing corporate social responsibility disclosure (CSRD) in companies’ annual reports, sustainability reports, and financial statements. Specifically, it investigates whether slack resources, industry sensitivity, and environmental performance affect CSRD. The sample consists of 25 companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, resulting in 75 observations. This research employs a quantitative approach using secondary data obtained from published company reports. The data were analyzed using statistical methods to test the proposed hypotheses. The results indicate that slack resources do not have a significant effect on CSRD, suggesting that the availability of excess resources does not necessarily lead to broader or higher-quality disclosures. Similarly, industry sensitivity does not significantly influence CSRD, implying that high-profile companies are not always more transparent in disclosing social responsibility activities than low-profile firms. In contrast, environmental performance has a significant effect on CSRD, indicating that companies with better environmental performance tend to disclose more comprehensive CSR information. These findings highlight the importance of environmental accountability in driving corporate transparency.